Modern slavery and exploitative work regimes: an intersectional approach: Modern Slavery and Exploitative Work Regimes: policy implications of multiple and differential intersections. Issue 2 (17th February 2023) - Arun, Shoba; Olsen, Wendy
ABSTRACT: This Special Issue covers an intersectional approach to extreme labour exploitation. We provide concrete empirical studies and new theoretical frameworks. This overview paper analyses how modern slavery theories might influence policy options. The theories examined in this Special Issue include supply-chain theories, feminist approaches to work, diffusion of innovation theory, intersectional gender-and-development theory, and the social construction of narratives around bonded and forced labour. Evidence is given from the garment industry, farming, and other sectors based on field research and questionnaire surveys dated 2015–2020. Women in paid jobs are widely exposed to extreme exploitation, coerced overtime, having their papers held by the employer, and subject to threats/violence. In care work, the gender worktime difference is large, and evidence is given from India of girl children's work hours being much longer, on average, than boys' hours. Extreme exploitation rests upon gaping social and economic inequalities which deserve policy attention.